Treating Triple Negative Breast Cancer Cells with Erlotinib Plus a Select Antioxidant overcomes Drug Resistance by Targeting Cancer Cell Heterogeneity. - Bao, B.; Mitrea, C.; Wijesinghe, P.; Marchetti, L.; Girsch, E.; Farr, R.L.; Boerner, J.L.; Mohammad, R.; Dyson, G.; Terlecky, S.R.; Bollig-Fischer, A (My University, 2017)
Among breast cancer patients, those diagnosed with the triple-negative breast cancer (TNBC) subtype have the worst prog-nosis.TNBC does not express estrogen receptor-alpha, progesterone receptor, or the HER2 oncogene; therefore, TN B C lacks targets for molecularly-guided therapies. The concept that EGFR oncogene inhibitor drugs could be used as targeted treatment against TNB C has been put forth based on estimates that 30-60% of TNBC express high levels of EGFR. However, results from clinical trials testing EGFR inhibitors, alone or in combination with cytotoxic chemotherapy, did not improve patient outcomes. Results herein offer an explanation as to w hy EGFR inhibitors failed TN B C patients and support how combining a select antioxidant and an EGFR-specific small molecule kinase inhibitor (SMKI) could be an effective, novel therapeutic strategy. Treatment with CAT-SKL— a re-engineered protein form of the antioxidant enzyme catalase— inhibited cancer stem-like cells (CSCs), and treatment with the EGFR-specific SMKI erlotinib inhibited non-CSCs. Thus, combining the antioxidant CAT-SKL with erlotinib targeted both CSCs and bulk cancer cells in cultures of EGFR-expressingTNBC-derived cells. We also report evidence that the mechanism for CAT-SKL inhibition of CSCs may depend on antioxidant-induced downregulation of a short alternative m RNA splicing variant of the methyl-CpG binding domain 2 gene, isoform MBD2c.